THE LINGUISTIC SYSTEM OF THE PHILOSOPHY OF GRAMMAR - Shigabutdinova, Dina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article analyzes the views of the Danish linguist Otto Espersen on the philosophy of grammar, the historical development of the English language and the methodology of teaching foreign languages. Espersan's linguistic thinking on the development of language is still relevant today, despite being heavily criticized at the time.